Direct Allylation of Active Methylene Compounds with Allylic Alcohols by Use of Palladium/Phosphine‐Borane Catalyst System. Issue 10 (10th April 2018) - Shimizu, Aika; Hirata, Goki; Onodera, Gen; Kimura, Masanari
Abstract: The C−C bond formation between active methylene compounds and allylic alcohols has been newly developed by using a palladium complex as a catalyst together with a phosphine‐borane ligand. The best phosphine‐borane ligand for this direct allylation has been revealed to be Ph2 P(CH2 )4 (9‐BBN) to produce a variety of desirable allylated products in high yields. Abstract :